PENGARUH LATIHAN WALL SIT UP TERHADAP DAYA TAHAN OTOT PERUT PADA ATLET RENANG ASEAN SWIMMING CLUB (ASC) RIAU - Intan Sholihah; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the observations of the Asian Swimming Club (ASC) athletes, these athletes have not optimized their swimming in every style. One of them is when doing the reverse. It can be seen that the lack of endurance when doing these reversals is like the endurance of the abdominal muscles. Lack of resistance of the abdominal muscles is seen when returning, this makes the swimming speed decrease, so that the time is longer. The purpose of this study was to determine the effect of wall sit up training on abdominal muscle endurance in Asean Swimming Club (ASC) Riau. The population in this study were 8 athletes in the Asean Swimming Club (ASC) Riau. The sampling technique is saturated sampling that is when all members of the population are used as samples, this is often done when the population is relatively small, less than 30 peoples, or the researcher wants to make generalizations with very little errors. So the sample in this study was determined as many as 8 peoples. The instrument in this study was a sit-up, the collected results were analyzed using the t-test. Based on the t-test results in a t-count of 4.592 with a t-table of 1.895, then H is accepted, at the alfa (a) 0.05 level. It can be concluded that there is an effect of wall sit up training on abdominal muscle endurance in the Asean Swimming Club (ASC) Riau. Based on the conclusion above, that wall sit up training can increase the endurance of the abdominal muscles, if given continuous training.Key Words: Wall Sit Up Training, Stomach Muscle Resistance